Education As a Tool For Forming Community's Religious And Political Character - Lubis, Mayang Sari; Harahap, Nora Adi Anna; Ardhiyah, Ummu; Thamimi, Ika Maulida; Nasir, Muhammad (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
Islam is one of the largest religions practiced by people all over the world. One of its teachings is to guarantee the happiness of life for its adherents, both in this world and in the hereafter, which is reflected in the Quran and Hadith. In addition, Islam plays a very important role in the social life of the community, with various phenomena, circumstances, and social facts that exist around it. In daily social interactions, many advances occur and clearly affect people's behavior and attitude patterns. The research method used in this study is a literature study, namely by collecting data through understanding and analyzing theories from various related literature. The findings explain that by applying Islamic religious values in a real and consistent manner in society, we can see positive social changes. Education is a good character-building tool, in addition to functioning as a guideline for life. Islamic religious education also plays a filter role in dealing with negative impacts due to social changes that occur in society.